The Relationship Between Social Power and Sexual Objectification: Behavioral and ERP Data - Xiao, Lijuan; Li, Baolin; Zheng, Lijun; Wang, Fang (Frontiers in Psychology, 2019)
Abstract Sexual objectification is very common in modern Western societies, especially toward women. Previous research has suggested that in Western cultures, social power could lead to objectification. Specifically, power activates an approaching tendency toward useful targets, in turn leading to instrumental objectification and sexual objectification of targets. However, previous research has mostly focused on Western cultures, and the neural correlates underlying this phenomenon remain unclear. To examine whether the effects of power can be generalized to Chinese cultural contexts and how power promotes the objectification of sexualized bodies, we conducted two studies using Chinese samples. In Study 1, we replicated the behavioral effects of social power on sexual objectification. Specifically, we found that power increased sexual objectification toward sexualized female rather than male bodies. In Study 2, we examined the absence of an N170 amplitude inversion effect as a possible neural correlate of sexual objectification and replicated the effects of power on sexual objectification through event-related potentials (ERPs). For participants in a high-power group, the N170 amplitude inversion effect emerged when processing sexualized male bodies (less sexual objectification) but not female bodies (more sexual objectification); this effect was not seen for those participants in a low-power group. Our findings provide behavioral and neural data that power leads to increased sexual objectification toward sexualized women in Chinese participants.